PENGARUH KOORDINASI PIMPINAN TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT BANGUN PURBA KABUPATEN ROKAN HULU - -, Masrayani; -, Makmur; Yasdomi, Kiki (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
This study aims to analyze coordination leadership which built in the office camat bangun purbakabupaten rokan hulu, analyze performance employee in the office camat bangun purbakabupaten rokan hulu and for find out effect coordination leadership to performance employeein the office camat bangun purba kabupaten rokan hulu. This study to use technique analysisdata simple linear regression with sampling method it can be seen factor coordinationleadership take effect significant and positif to performance employee in the office camat bangunpurba kabupaten rokan hulu be evidenced with t test (2.423>0,26) and coordination leadershipaffect performance employee in the office camat bangun purba kabupaten rokan hulu as big as49% and the rest 51% of other factors, this is evidenced with R test square with the value of thedeterminant kofesien 0,496.